Application of Meta-Gaming Concept to the Publishing Platform: Analysis of the Steam Games Platform - Muhammad Nazhif Rizani; Mohd Nor Akmal Khalid; Hiroyuki Iida (Information, 2023)
The digital marketplace has rapidly grown, transitioning the market of video games from physical localized experiences to more networked, expanded, virtual spaces. With a highly competitive business market, platform governance policy allows for the emergence of rapidly growing publishing platforms for digital video games such as the Steam platform. This study demonstrated the importance of the meta-gaming of a platform based on the Steam platform; 18,658 Steam-listed games were acquired and analyzed from the Steam Store, Steam Spy, and Steam achievement databases. A detailed analysis was conducted where key research questions were formulated concerning the game information. This study found that digital badging (i.e., achievements) increases players’ engagement with the publishing platform with good auxiliary data (such as types, rating, releases, and prices). Based on such findings, an opportunity for a new business model is envisioned.